Penerapan Flipped Classroom Berbantuan Google Sites pada Pembelajaran Matematika di Kelas VII SMP PGRI PGRI 1 Palembang - Kristira, Gita; Septiati, Ety; Isroqmi, Asnurul (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
The goal to be achieved in this study is to find out the learning outcomes and learning activities of students with the application of flipped classrooms assisted by Google sites in learning mathematics for class VII SMP PGRI 1 Palembang. The method in this research is quantitative descriptive. Subjects in this study amounted to 31 students. Data collection techniques in this study were learning achievement tests and student learning activity sheets. Based on the results of research and data analysis, it can be concluded that the application of flipped classroom with the help of google sites student learning outcomes are quite good. It is known that the average is 67.26 with 61% completeness and student learning activities are classified as good with a percentage of 68%.